Failure to improve the effect of thrombolysis by memantine in a rat embolic stroke model - Back, Tobias; Otto, Dörte; Kittner, Daniela; Schüler, Olaf G.; Hennerici, Michael G.; Mennel, Hans-Dieter (Neurological research, 2007)
OBJECTIVES: Partial and delayed recanalization is a regular finding after thrombolysis in stroke patients who may benefit from additional therapy with neuroprotectants. To translate this scenario into an experiment, memantine was combined with thrombolysis in an embolic stroke model and tissue outcome was assessed in terms of complete and incomplete damage. - METHODS: Tissue plasminogen activator (tPA, 5 mg/kg, b.w.) was administered 1.5 or 3.5 hours after embolic middle cerebral artery (MCA) occlusion in rats. In both groups, rats were assigned to additional therapy with memantine (10 mg/kg, i.p.) or saline injection. Ischemia and eventual reperfusion were continuously monitored by laser-Doppler flowmetry. Reperfusion was defined as a lasting increase in post-thrombolytic cerebral blood flow to >60% of baseline (complete) or to a lesser degree (partial). Experiments were terminated 6 hours post-occlusion to obtain quantitative histopathology. - RESULTS: tPA induced complete or partial recanalization in 54% of treated animals. Successful reperfusion reduced total ischemic lesion volume by 42% compared with non-reperfused animals (p<0.05), but increased significantly the percentage of scattered neuronal injury from 25.6 (non-reperfusion) to 36.3% (reperfusion, p<0.05). Memantine did not improve the effect of tPA-induced recanalization on infarct morphology whether applied at 1.5 or 3.5 hours post-occlusion. - DISCUSSION: We conclude from our experiments that add-on therapy with memantine did not alter the effect of thrombolysis in an embolic stroke model. Recanalization appears to be a prerequisite to confer neuroprotective effects.